2020
DOI: 10.3390/polym13010080
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet Printing of an Electron Injection Layer: New Role of Cesium Carbonate Interlayer in Polymer OLEDs

Abstract: Among solution-processable techniques, inkjet printing is a potential method for manufacturing low-cost and high-resolution polymer organic light-emitting diodes (PLEDs) for displays/solid-state lighting applications. Herein, we demonstrate use of the inkjet printed cesium carbonate (Cs2CO3) film as an electron injection interlayer. We have elaborated the Cs2CO3 ink using an alcohol-based solvent for the industrial-grade printhead. The printed Cs2CO3 layer morphology was investigated by means of an optical mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…The stability of a model PLED based on Super Yellow-the most often used polymer as an emission layer in PLEDs [22]-has been studied in terms of the conductive-capacitive properties of the organic layers. It was found that the AC response is extremely sensitive to the minor changes in PLED caused by the applied electric field, and contact with the ambient atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of a model PLED based on Super Yellow-the most often used polymer as an emission layer in PLEDs [22]-has been studied in terms of the conductive-capacitive properties of the organic layers. It was found that the AC response is extremely sensitive to the minor changes in PLED caused by the applied electric field, and contact with the ambient atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…As the concentration of cesium carbonate increased, the brightness of the composite device was also improved (Figure b), which corresponded to the results obtained by PL and TRPL. At the same time, the turn-on voltage of the device was also reduced because of the excellent ability of cesium carbonate to improve electron injection. As shown in Figure d, although an extra layer was added to the quantum dot device, the current density of the device did not decrease but increased, which further proved the good electron injection ability of cesium carbonate. Moreover, the external quantum efficiency (EQE) and power efficiency (PE) had a significant improvement (Figure S8).…”
Section: Resultsmentioning
confidence: 89%
“…It is characterized by low amounts of waste and the use of a small amount of material needed for the process. Application areas for printed electronics include, so far, resistors [5], organic light-emitting diodes (OLEDs) [6], display [7], solar cells [8], thin-film transistors [9], capacitors [10,11], microwave circuits [12,13], and many others.…”
Section: Introductionmentioning
confidence: 99%